The Influence Of Location, Facilities, Price, And Product Variation On Purchase Decisions At MSME Shops In Madiun City (Case Study of MSME Stalls in Semendung Park, Madiun City) - Dian Citaningtyas Ari Kadi; Rizal Ula Ananta Fauzi; Khairul Anam (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Purchasing decisions are one of the stages of consumer behavior that underlies consumers to make purchasing decisions before post-purchase behavior and how individuals, groups, and organizations choose, buy, use, and how goods or services satisfy their needs and wants.. This study aims to provide partial evidence inBuying decisionInfluenced ByLocation, Facilities, Prices, and Product VariationsOnAt the UMKM Stalls in Madiun City.This study uses a quantitative approach with a survey research design. Research populationare residents of the city of Madiun and have visited Semendung Park. The technique used in this research is purposive sampling technique. Using a purposive sampling technique, the researcher distributed questionnaires by sharing gform links on social media with the criteria of the people of the city of Madiun and having visited the Semendung Taman UKM 1x.methodThis study uses a quantitative approach using the SmartPLS4.0 program, because the population is unknown, the researchers used the Lemeshow formula to determine the sample size, namely 385 respondents.This research was conducted based on the results of a survey which showed that there were several purchase decision problems that were influenced by location, facilities, prices and product variations at UMKM stalls in Madiun City.The results of the study prove that (1) Location has a positive and significant effect on purchasing decisions at UMKM stalls in Madiun City; (2) Facilities have a positive and insignificant effect on purchasing decisions; (3) Price has a positive and significant effect on purchasing decisions; (4) Product variations have a positive and significant effect on purchasing decisions